EVALUASI KEBIJAKAN RUMAH POTONG HEWAN PADA DINAS PERTANIAN DAN PETERNAKAN KABUPATEN PARIGI MOUTONG - Muhtar, Muhtar (Katalogis, 2016)
This research aimed to: 1) evaluate the policy of animal butchery house at Agriculture and Animal Husbandry Office in Parigi District at Parigi Moutong Regency; and 2) find out the obstacles in the evaluation of animal butchery house at Agriculture and Animal Husbandry Office in Parigi District at Parigi Moutong Regency. This research was done at Agriculture and Animal Husbandry Office of Parigi Moutong Regency by taking 5 informen. This research used the theory proposed by Dunn in Abidin by evaluating the policy from efficiency, profitability, effectiveness, equity and detriments. The result of the research shows that: 1) seeing from the aspects of efficiency, profitability, effectiveness, equity and detriments the evaluation policy applied in Parigi animal butchery house of Parigi Moutong Regency did not run well; and 2) the evaluation policy was not effective due to: a) the lack of socialization on the Regional Regulation No. 20/2005 so that this Animal Butchery House had not been considered necessary by the meat businessmen and the community; and b) the lack of tools and utilities in the house that made the businessmen were not interested in using this facility for their animals.Â